A Novel Microindenter to Assess the Mechanical Properties of Soft Materials - Celik, Umit (Ieee-Inst Electrical Electronics Engineers Inc, 2024)
Soft materials, such as polymers, gels, biomaterials, and elastomers, have unique mechanical properties. Micro/nanoindentation techniques allow for the characterization of mechanical parameters. Understanding these properties is essential for designing and optimizing soft materials for specific applications. In this study, it is aimed to develop a low-cost and easy-to-use microindenter that can enable to measure the local mechanical properties of soft samples. Micro/nanoindentation with atomic force microscope (AFM) has advantages, such as high sensitivity and measurement capability of local mechanical properties. However, it has some disadvantages, such as being difficult to use, requiring a trained specialist, and high consumable costs. In this study, it is intended to inherit the advantages of AFM-based indentation technique and overcome its limitations. We designed robust and low-cost metal cantilevers for the force measurement. A low-cost voice coil motor is used as force actuators. An optical slot sensor is employed to measure the cantilever deflection without the need for laser and photodetector adjustment as in AFMs. In the study, 5:1 and 25:1 PDMS samples were prepared to test the apparatus. The elastic modulus for the PDMS 5:1 and 25:1 samples was measured as 3.72 +/- 0.05 MPa and 0.96 +/- 0.15 MPa.
Keywords: Atomic force microscope (AFM); cantilever-based microindentation device; elastic modulus; mechanical properties; soft materials